MEDIA PEMBELAJARAN JENIS-JENIS KAKTUS DENGAN PENERAPAN MARKER BASED TRACKING AUGMENTED REALITY - Ashadul Ushud, Achmad Aditya (Universitas Komputer Indonesia, 2020)
Cactus is known as a thorny plant that lives in less water conditions because it can save water inside its trunk. Most people know cactus as a thorny plant, even though not all cacti have thorns. This is because many people do not know the types of cactus. Especially at this time, many cacti used as houseplants. Because there are several types of cactus have a beautiful shape, besides that the cactus is also known to be easily treated because it does not need to be watered frequently. This study aims to recognize and identify the types of cacti in the world through an interactive learning media that is easy to do, namely Augmented Reality. During this time many cactus were introduced only through books, pictures or photos. Meanwhile, to present the cactus itself is difficult. Especially for some types of cactus that live in certain areas and including rare. So to recognize the cactus in detail is felt difficult to do. By using Augmented Reality technology with Marker Based Tracking method based on Android phone, it is hoped that it can help the learning process. Users can identify the types of cactus through the mobile screen. Key Words : Augmented Reality, Marker Based Tracking, cactus, Android